Silicon-carbon negative electrode material and preparation method and application thereof
By uniformly inlaid nanosilicon particles in silicon carbon anode material and doped with fluorine and phosphorus elements, the complex and safety problems in the existing technology are solved, the cycle and rate performance of the battery is improved, the process is simplified and electrochemistry is improved performance.
Patent Information
- Application Number
- CN202411333021.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
AI Technical Summary
The existing preparation methods of silicon carbon negative electrode materials have problems such as high equipment requirements, difficulty in uniform embedded nano-silicon, complex process and flammable and explosive, resulting in poor electronic conductivity and large volume changes during embedded/delithation, which affects the energy density of the battery. and cycle performance.
The biomass carbon source, fluorine source, phosphorus source and liquid phase silane formation system are heat treated, and solid-liquid separation and washing and drying are obtained to obtain a silicon carbon negative electrode material with nanosilicon particles uniformly embedded in the spherical carbon matrix, doped with fluorine and phosphorus elements to improve conductivity.
The uniformity and electrochemical performance of silicon carbon negative electrode materials are improved, the cycle performance and rate performance of the battery are improved, the preparation process is simplified, and the material safety and environmental protection are better.
Smart Images

Figure CN119208563A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are a type of power source widely used in digital products, electric vehicles, energy storage power stations, etc. With the rapid development of electric vehicles in recent years, people's demand for higher driving range has become increasingly urgent. An effective way to improve driving range is to increase the energy density of lithium-ion batteries. To this end, electrode materials with higher specific capacity are needed. At present, most lithium batteries on the market use graphite as the negative electrode, and its theoretical lithium insertion capacity is 372mAh / g. With the advancement of graphite production technology, the actual specific capacity of existing graphite products has approached the theoretical value. Silicon is a negative electrode material with extremely high lithium insertion capacity (3579mAh / g). In order to break through the limitations of the theoretical energy density of graphite products, a large number of researchers have begun to develop commercially available silicon-based materials.
[0003] The main problem of silicon-based materials is their poor electronic conductivity and huge volume changes during the insertion / extraction of lithium. In order to solve the above problems, nano-silicon carbon materials came into being. At present, the preparation methods of nano-silicon carbon can be divided into solid-phase method and gas-phase method. In the solid-phase method, silicon particles are first ground to nanoscale, then embedded in the interlamellar layers of natural graphite by spray drying, and then carbon-coated with carbon sources such as asphalt. The gas-phase method uses porous carbon as the matrix and silicon tetrahydride as the silicon source. First, nano-silicon particles are deposited in the pores of porous carbon by chemical vapor deposition, and then carbon-coated with carbon sources such as methane and acetylene.
[0004] The disadvantages of the solid phase method include: 1) the grinding of nano-silicon has high requirements for equipment; 2) it is difficult to embed nano-silicon evenly into natural graphite. The disadvantages of the gas phase method include: 1) it is necessary to prepare porous carbon materials with suitable pore structures first, and the process is relatively complicated; 2) it is difficult to ensure the uniformity of nano-silicon deposition and carbon coating; 3) silicon tetrahydride is flammable and explosive, and has a high risk.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One object of the present invention is to provide a silicon-carbon negative electrode material to solve the above-mentioned preparation defects of the silicon-carbon negative electrode material in the prior art; the silicon-carbon negative electrode material of the present invention has better electrochemical properties.
[0007] Another object of the present invention is to provide a method for preparing the silicon-carbon negative electrode material, which is simple and easy to implement, environmentally friendly, and the obtained silicon-carbon negative electrode material has the characteristics of high capacity and long cycle.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] A silicon-carbon negative electrode material comprises a carbon matrix, nano silicon particles and doping elements, wherein the nano silicon particles are uniformly embedded in the carbon matrix, the doping elements are doped in the carbon matrix, and the doping elements include fluorine and phosphorus.
[0010] In some embodiments, the mass of the nano-silicon particles accounts for 20% to 60% of the mass of the silicon-carbon negative electrode material, the mass of the fluorine element accounts for 0.2% to 0.8% of the mass of the silicon-carbon negative electrode material, and the mass of the phosphorus element accounts for 0.5% to 2% of the mass of the silicon-carbon negative electrode material.
[0011] In some embodiments, the particle size D50 of the silicon-carbon negative electrode material is 1 to 20 μm.
[0012] In some embodiments, the particle size D50 of the nano-silicon particles is 5 to 20 nm.
[0013] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0014] The first system formed by the biomass carbon source, the fluorine source, the phosphorus source and the liquid silane is heat-treated to obtain the second system, the second system is subjected to solid-liquid separation, the solid is collected and washed and dried to obtain the silicon-carbon negative electrode material.
[0015] In some embodiments, the biomass carbon source includes a sugar source and / or cellulose, and the sugar source is selected from at least one of glucose, fructose and sucrose.
[0016] In some embodiments, the fluorine source includes polyvinylidene fluoride.
[0017] In some embodiments, the phosphorus source includes an A source and / or phytic acid, and the A source is selected from at least one of dimethyl phosphate, trimethyl phosphate and tricresyl phosphate.
[0018] In some embodiments, the liquid silane includes at least one of tetramethylsilane, tetraethylsilane, triethylsilane, dimethylsilane, methylsilane, phenylsilane and diphenylsilane.
[0019] In some embodiments, the mass ratio of the biomass carbon source, the liquid silane, the fluorine source and the phosphorus source is (50-150):(150-500):(0.5-1.5):(2-6).
[0020] In some embodiments, the first system is subjected to the heat treatment under sealed conditions.
[0021] In some embodiments, the heat treatment temperature is 350-550° C., and the heat treatment time is 6-12 hours.
[0022] In some embodiments, the heating rate of the heat treatment is 5 to 20° C. / min.
[0023] In some embodiments, the drying temperature is 50-90°C.
[0024] A negative electrode sheet comprises the silicon-carbon negative electrode material or the silicon-carbon negative electrode material prepared by the method for preparing the silicon-carbon negative electrode material.
[0025] A battery comprises the negative electrode sheet.
[0026] An electrical device comprises the battery.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The silicon-carbon negative electrode material of the present invention has good uniformity, and the nano-silicon particles are evenly embedded in the spherical carbon matrix. The carbon matrix can effectively alleviate the volume expansion of the silicon particles during the lithium insertion / extraction process, thereby improving the cycle performance of the battery; the carbon matrix is doped with fluorine and phosphorus elements, which can improve the electronic / ionic conductivity of the silicon-carbon negative electrode material, thereby improving the rate performance of the battery.
[0029] (2) The preparation method of the silicon-carbon negative electrode material of the present invention is simple and easy, and the obtained negative electrode material has excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 This is a diagram of the preparation mechanism of the silicon-carbon negative electrode material of the present invention. DETAILED DESCRIPTION
[0032] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0033] According to one aspect of the present invention, the present invention relates to a silicon-carbon negative electrode material, comprising a carbon matrix, nano-silicon particles and doping elements, wherein the nano-silicon particles are uniformly embedded in the carbon matrix, and the doping elements are doped in the carbon matrix, and the doping elements include fluorine and phosphorus.
[0034] The silicon-carbon negative electrode material of the present invention has good uniformity, and nano silicon particles are evenly embedded in the spherical carbon matrix. The carbon matrix can effectively alleviate the volume expansion of silicon particles during the lithium insertion / extraction process, thereby improving the cycle performance of the battery; fluorine and phosphorus elements are doped in the carbon matrix to improve the electronic / ionic conductivity of the silicon-carbon negative electrode material, thereby improving the rate performance of the battery.
[0035] In some embodiments, the mass of the nano-silicon particles accounts for 20% to 60% of the mass of the silicon-carbon negative electrode material, including but not limited to 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc., or any range between the two. In some embodiments, the mass of the fluorine element accounts for 0.2% to 0.8% of the mass of the silicon-carbon negative electrode material, such as 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, etc., or any range between the two. The mass of the phosphorus element accounts for 0.5% to 2% of the mass of the silicon-carbon negative electrode material, such as 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.5%, 1.6%, 1.8%, 1.9%, 2%, etc., or any range between the two. The present invention adopts nano silicon particles, fluorine element, phosphorus element and carbon matrix with appropriate mass content, which is more conducive to ensuring that the negative electrode material has excellent electrochemical performance.
[0036] In some embodiments, the shape of the silicon-carbon negative electrode material includes a spherical shape. The silicon-carbon negative electrode material of the present invention has a suitable particle size range, and the particle size D50 of the silicon-carbon negative electrode material is 1 to 20 μm, including but not limited to 1 μm, 2 μm, 4 μm, 5 μm, 8 μm, 10 μm, 12 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm, etc., or any range value between the two.
[0037] In some embodiments, the nano silicon particles have a suitable particle size D50, and the particle size D50 is 5 to 20 nm, for example, 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, etc.
[0038] According to another aspect of the present invention, the present invention also relates to a method for preparing a silicon-carbon negative electrode material, comprising the following steps:
[0039] The first system formed by the biomass carbon source, the fluorine source, the phosphorus source and the liquid silane is heat-treated to obtain the second system, the second system is subjected to solid-liquid separation, the solid is collected and washed and dried to obtain the silicon-carbon negative electrode material.
[0040] The method for preparing the silicon-carbon negative electrode material of the present invention is simple and easy to implement, and the obtained negative electrode material has excellent electrochemical performance. Figure 1 As shown, under the supercritical state, due to the relatively weak bond energy of biomass carbon source molecules, they are easy to dissociate to form active groups, thus leading to the occurrence of nucleation reaction, and the formed nucleus gradually grows; at the same time, the silane molecules with stronger bond energy will also decompose into silicon atoms, and then adsorb to the surface of the carbon core to form clusters. Under high energy conditions, the carbon core will grow rapidly by aggregation and fusion, and finally form a spherical silicon-carbon negative electrode material with nano-silicon particles uniformly embedded inside; fluorine source and phosphorus source are also uniformly doped into the carbon matrix in this process to further improve the electrical performance.
[0041] In some embodiments, the biomass carbon source includes a sugar source and / or cellulose, and the sugar source is selected from at least one of glucose, fructose and sucrose. In some embodiments, the biomass carbon source is selected from cellulose and a sugar source, and the mass ratio of cellulose to the sugar source is (4-6): (7-8), such as 4:7, 5:7.5, 6:8, etc. The coordination of cellulose and sugar source is more conducive to play a role, ensure the performance of the carbon matrix, and is conducive to element doping and inlaying nano-silicon particles.
[0042] In some embodiments, the fluorine source includes polyvinylidene fluoride. Polyvinylidene fluoride is a pure thermoplastic fluorine-containing polymer, a polymer compound obtained by polymerizing vinylidene fluoride, which has excellent chemical corrosion resistance, excellent high temperature color change resistance and oxidation resistance. It is prepared with other raw materials to provide fluorine elements, which is beneficial to improve the electrical properties of the negative electrode material.
[0043] In some embodiments, the phosphorus source includes an A source and / or phytic acid, and the A source is selected from at least one of dimethyl phosphate, trimethyl phosphate, and tricresyl phosphate. In some embodiments, the mass ratio of the A source to the phytic acid is (4-8):1, such as 4:1, 5:1, 6:1, 7:1 or 8:1. The A source and phytic acid of the present invention are matched in a suitable ratio, which is more conducive to ensuring the electrochemical performance of the negative electrode material.
[0044] In some embodiments, the liquid silane includes at least one of tetramethylsilane, tetraethylsilane, triethylsilane, dimethylsilane, methylsilane, phenylsilane and diphenylsilane.
[0045] In some embodiments, the mass ratio of the biomass carbon source, liquid silane, fluorine source and phosphorus source is (50-150): (150-500): (0.5-1.5): (2-6), for example 50:150:0.5:2, 60:180:0.7:3, 100:200:1:3, 120:300:1.2:5, 150:500:1.5:6, etc. In the present invention, the biomass carbon source, liquid silane, fluorine source and phosphorus source adopt a suitable mass ratio, which is more conducive to mutual cooperation, and a silicon-carbon negative electrode material with suitable structural characteristics and component content is obtained after heat treatment to ensure its high capacity and high cycle performance.
[0046] In some embodiments, the first system is heat treated under sealed conditions. That is, the first system is placed in a pressure reaction device, evacuated, and then placed in a heat treatment device for heat treatment. The evacuation is to 0.1-10Pa, such as 0.1Pa, 0.5Pa, 1Pa, 3Pa, 5Pa, 8Pa, 10Pa, etc.
[0047] In some embodiments, the temperature of the heat treatment is 350-550°C, including but not limited to 350°C, 380°C, 400°C, 410°C, 450°C, 480°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, etc., or any range between the two. The time of the heat treatment is 6-12h, including but not limited to 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h or 15h, etc., or any range between the two. The heating rate of the heat treatment is 5-20°C / min, including but not limited to 5°C / min, 8°C / min, 10°C / min, 15°C / min, 18°C / min or 20°C / min, etc., or any range between the two. The present invention adopts suitable heat treatment conditions to ensure the physical and chemical properties and electrical properties of the final silicon-carbon negative electrode material.
[0048] In some embodiments, anhydrous ethanol is used for washing for multiple times, such as 4 to 10 times.
[0049] In some embodiments, the drying temperature is 50-90°C, including but not limited to 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 90°C, etc., or any range therebetween.
[0050] According to another aspect of the present invention, the present invention also relates to a negative electrode sheet, comprising a silicon-carbon negative electrode material, or a silicon-carbon negative electrode material prepared by the method for preparing the silicon-carbon negative electrode material.
[0051] The negative electrode sheet of the present invention comprises a negative electrode current collector and a negative electrode material layer located on at least one side of the negative electrode current collector, wherein the negative electrode material layer comprises the above-mentioned silicon-carbon negative electrode material, a conductive agent and a binder. The specific preparation method of the negative electrode sheet comprises: mixing the silicon-carbon negative electrode material, the conductive agent and the binder with a solvent in a certain proportion to obtain a negative electrode slurry, uniformly coating the negative electrode slurry on at least one side of the negative electrode current collector, and drying and rolling to obtain a negative electrode sheet.
[0052] According to another aspect of the present invention, the present invention also relates to a battery comprising the above-mentioned negative electrode sheet.
[0053] The battery of the present invention has excellent cycle performance, rate performance and safety performance.
[0054] In some embodiments, the battery of the present invention includes the above-mentioned negative electrode sheet, positive electrode sheet, separator and electrolyte.
[0055] According to another aspect of the present invention, the present invention also relates to an electric device, comprising the above-mentioned battery. The electric device includes electric vehicles, portable devices, etc.
[0056] The following is further explained in conjunction with specific embodiments and comparative examples.
[0057] Example 1
[0058] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0059] (1) 150 g of glucose, 1 g of polyvinylidene fluoride, and 5 g of phytic acid were dissolved in 500 g of tetramethylsilane to obtain a first system.
[0060] (2) The first system was encapsulated in a stainless steel pressure reactor, evacuated to 5 Pa, and then placed in a high-temperature furnace, heated to 450°C, and kept at this temperature for 8 h at a heating rate of 10°C / min to obtain a second system.
[0061] (3) The second system is centrifuged, washed several times with anhydrous ethanol, and then dried at 80° C. to obtain a spherical silicon-carbon negative electrode material with a mosaic structure. The particle size D50 of the spherical silicon-carbon negative electrode material is 11 μm, and the mass content of silicon is 31.3%.
[0062] Example 2
[0063] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0064] (1) 100 g of sucrose, 0.8 g of polyvinylidene fluoride, and 4 g of phytic acid were dissolved in 400 g of diphenylsilane to obtain a first system.
[0065] (2) The first system was encapsulated in a stainless steel pressure reactor, evacuated to 5 Pa, and then placed in a high-temperature furnace, heated to 500° C., and kept at this temperature for 8 h at a heating rate of 10° C. / min to obtain a second system.
[0066] (3) The second system is centrifuged, washed several times with anhydrous ethanol, and then dried at 80° C. to obtain a spherical silicon-carbon negative electrode material with a mosaic structure. The particle size D50 of the spherical silicon-carbon negative electrode material is 14 μm, and the mass content of silicon is 34.6%.
[0067] Example 3
[0068] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0069] (1) 120 g of fructose, 0.9 g of polyvinylidene fluoride, and 4.5 g of dimethyl phosphate were dissolved in 450 g of tetraethylsilane to obtain a first system.
[0070] (2) The first system was encapsulated in a stainless steel pressure reactor, evacuated to 5 Pa, and then placed in a high-temperature furnace, heated to 450°C, and kept at this temperature for 8 hours at a heating rate of 5°C / min to obtain a second system.
[0071] (3) The second system is centrifuged, washed several times with anhydrous ethanol, and then dried at 80° C. to obtain a spherical silicon-carbon negative electrode material with a mosaic structure. The particle size D50 of the spherical silicon-carbon negative electrode material is 9 μm, and the mass content of silicon is 28.4%.
[0072] Example 4
[0073] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0074] (1) 40 g of fructose, 10 g of glucose, 70 g of cellulose, 0.9 g of polyvinylidene fluoride, 4 g of trimethyl phosphate, and 0.5 g of phytic acid were dissolved in 450 g of tetraethylsilane to obtain a first system.
[0075] (2) The first system was encapsulated in a stainless steel pressure reactor, evacuated to 6 Pa, and then placed in a high-temperature furnace, heated to 480°C, and kept at this temperature for 7 hours at a heating rate of 5°C / min to obtain a second system.
[0076] (3) The second system is centrifuged, washed several times with anhydrous ethanol, and then dried at 80° C. to obtain a spherical silicon-carbon negative electrode material with a mosaic structure. The particle size D50 of the spherical silicon-carbon negative electrode material is 13 μm, and the mass content of silicon is 32.6%.
[0077] Example 5
[0078] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0079] (1) 30 g of sucrose, 20 g of glucose, 80 g of cellulose, 1 g of polyvinylidene fluoride, 4 g of tricresyl phosphate, and 1 g of phytic acid were dissolved in 500 g of tetraethylsilane to obtain a first system.
[0080] (2) The first system was encapsulated in a stainless steel pressure reactor, evacuated to 6 Pa, and then placed in a high-temperature furnace, heated to 490°C, and kept at this temperature for 6.5 h at a heating rate of 5°C / min to obtain a second system.
[0081] (3) The second system is centrifuged, washed several times with anhydrous ethanol, and then dried at 80° C. to obtain a spherical silicon-carbon negative electrode material with a mosaic structure. The particle size D50 of the spherical silicon-carbon negative electrode material is 12 μm, and the mass content of silicon is 30.4%.
[0082] Comparative Example 1
[0083] A method for preparing a silicon-carbon negative electrode material, which differs from Example 3 in that:
[0084] In step (1), polyvinylidene fluoride and dimethyl phosphate are not added.
[0085] The particle size D50 of the silicon-carbon negative electrode material finally obtained is 10 μm, and the mass content of silicon is 29.4%.
[0086] Comparative Example 2
[0087] A method for preparing a silicon-carbon negative electrode material, which differs from Example 3 in that:
[0088] In step (1), 200 g of fructose, 0.2 g of polyvinylidene fluoride, and 10 g of dimethyl phosphate are dissolved in 400 g of tetraethylsilane to obtain a first system.
[0089] The particle size D50 of the silicon-carbon negative electrode material finally obtained is 12 μm, and the mass content of silicon is 31.7%.
[0090] Experimental example
[0091] The negative electrode materials obtained in each embodiment and comparative example are respectively prepared into batteries, and the specific method includes:
[0092] Silicon-carbon negative electrode material, sodium carboxymethyl cellulose, binder, carbon black and deionized water were placed in a stirring tank of a stirrer in a mass ratio of 95:2:2:1:100 and stirred to obtain a negative electrode slurry. The slurry was coated on a current collector copper foil, dried at 80°C and rolled to obtain a negative electrode sheet. A metal lithium sheet was used as a counter electrode, a polypropylene film was used as a separator, and a 1 mol / L lithium hexafluorophosphate solution (wherein the solvent was a mixture of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1) was used as an electrolyte. CR2032 button batteries were assembled in an argon-filled glove box and the electrochemical properties were tested.
[0093] The electrochemical performance test results of the battery are shown in Table 1.
[0094] Table 1 Electrochemical performance test results of the battery
[0095]
[0096] It can be seen from Table 1 that the silicon-carbon negative electrode material obtained by the methods of each embodiment of the present invention has excellent electrochemical properties. The first-week discharge specific capacity of the obtained battery at 0.5A / g is above 1430mAh / g, the first-week charge specific capacity is above 1250mAh / g, and the first-week coulombic efficiency is above 85%; the capacity retention rate after 500 cycles at a rate of 2A / g is above 92%.
[0097] The electrochemical performance of the batteries obtained from the negative electrode materials of Comparative Examples 1 to 2 is relatively poor.
[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A silicon-carbon negative electrode material, characterized in that: The invention comprises a carbon matrix, nano silicon particles and doping elements, wherein the nano silicon particles are uniformly embedded in the carbon matrix, the doping elements are doped in the carbon matrix, and the doping elements include fluorine and phosphorus.
2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The mass of the nano silicon particles accounts for 20% to 60% of the mass of the silicon-carbon negative electrode material, the mass of the fluorine element accounts for 0.2% to 0.8% of the mass of the silicon-carbon negative electrode material, and the mass of the phosphorus element accounts for 0.5% to 2% of the mass of the silicon-carbon negative electrode material.
3. The silicon-carbon negative electrode material according to claim 1, characterized in that: The shape of the silicon-carbon negative electrode material includes a spherical shape; And / or, the particle size D50 of the silicon-carbon negative electrode material is 1 to 20 μm; And / or, the particle size D50 of the nano silicon particles is 5-20 nm.
4. A method for preparing a silicon-carbon negative electrode material, characterized in that: The following steps are involved: The first system formed by the biomass carbon source, the fluorine source, the phosphorus source and the liquid silane is heat-treated to obtain the second system, the second system is subjected to solid-liquid separation, the solid is collected and washed and dried to obtain the silicon-carbon negative electrode material.
5. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: Contains at least one of the following features (1) to (4): (1) The biomass carbon source includes a sugar source and / or cellulose, and the sugar source is selected from at least one of glucose, fructose and sucrose; (2) The fluorine source includes polyvinylidene fluoride; (3) the phosphorus source comprises an A source and / or phytic acid, wherein the A source is selected from at least one of dimethyl phosphate, trimethyl phosphate and tricresyl phosphate; (4) The liquid phase silane includes at least one of tetramethylsilane, tetraethylsilane, triethylsilane, dimethylsilane, methylsilane, phenylsilane and diphenylsilane.
6. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: The mass ratio of the biomass carbon source, the liquid silane, the fluorine source and the phosphorus source is (50-150):(150-500):(0.5-1.5):(2-6).
7. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: Contains at least one of the following features (1) to (4): (1) the first system performs the heat treatment under a sealed condition; (2) The temperature of the heat treatment is 350 to 550° C., and the time of the heat treatment is 6 to 12 hours; (3) The heating rate of the heat treatment is 5 to 20°C / min; (4) The drying temperature is 50 to 90°C.
8. A negative electrode sheet, characterized in that: The invention relates to a silicon-carbon negative electrode material comprising the silicon-carbon negative electrode material according to any one of claims 1 to 3, or a silicon-carbon negative electrode material prepared by the method for preparing the silicon-carbon negative electrode material according to any one of claims 4 to 7.
9. A battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to claim 8.
10. An electrical device, characterized in that: A battery comprising the battery of claim 9.
Citation Information
Cited By
Preparation method of vapor deposition silicon carbon material based on supercritical carrier gas
CN120767282A
A method for preparing a silicon-carbon material by vapor deposition based on a supercritical carrier gas
CN120767282B
Preparation method of improved silicon-carbon composite negative electrode material and lithium ion battery
CN120887407A
Preparation method of improved silicon-carbon composite negative electrode material and lithium ion battery
CN120887407B
